Origin of supermassive black holes in massive metal-poor protoclusters - Schleicher, Dominik R. G.; Reinoso, Bastián; Latif, M; Klessen, Ralf S.; Vergara, M. Z. C.; Das, A; Alister, Patricio; Díaz, V B; Solar, P A (Monthly notices of the Royal Astronomical Society, 2022)
While large numbers of supermassive black holes have been detected at z > 6, their origin is still essentially unclear. Numerical simulations have shown that the conditions for the classical direct collapse scenario are very restrictive and fragmentation is very difficult to be avoided. We thus consider here a more general case of a dense massive protostar cluster at low metallicity (≲10−3 Z⊙) embedded in gas. We estimate the mass of the central massive object, formed via collisions and gas accretion, considering the extreme cases of a logarithmically flat and a Salpeter-type initial mass function. Objects with masses of at least 104 M⊙ could be formed for inefficient radiative feedback, whereas ∼103 M⊙ objects could be formed when the accretion time is limited via feedback. These masses will vary depending on the environment and could be considerably larger, particularly due to the continuous infall of gas into the cloud. As a result, one may form intermediate mass black holes of ∼104 M⊙ or more. Upcoming observations with the James Webb Space Telescope and other observatories may help us to detect such massive black holes and their environment, thereby shedding additional light on such a formation channel.
Gesehen am 25.05.2022